Needle Stick And Sharp Related Injuries- Ethical Considerations, Prevention, And Management - Faisal Hanif; Umar Khurshid; Haroon Sabir Khan; Muhammad Zill-e-Humayun Mirza (Journal of Bahria University Medical and Dental College)
Laboratory and Health care workers (HCW) are exposed to many occupational related hazards. Both are at considerable risk of acquiring infections. Needle stick/prick injuries (NSIs) can lead to blood borne infections such as HIV, Hepatitis B and Hepatitis C. NSIs are one of the most common biological hazards inside laboratory. These injuries can be sustained while handling a sharp or needle and more commonly during recapping and waste disposal. Risk of transmission after these injuries from infected patients to HCW are 3-30% for hepatitis B, 3% for hepatitis C, and 0.3% for HIV1 . It is pertinent to mention that frequency of needle stick injuries is highest among nursing staff as reported by many published studies2 . Most common causes of injury among indoor hospital patients is phlebotomy or intravenous infusions. Still the exact magnitude of NSI in Pakistan is not clear because of poor or almost no reporting, surveillance system exist2,3